Why is pancreatic cancer so deadly?: the pathologist's view - Hruban, Ralph H.; Gaida, Matthias (The journal of pathology, 2019)
The remarkable aggressiveness of pancreatic cancer has never been fully explained. Although clearly multifactorial, we postulate that venous invasion, a finding seen in most pancreatic cancers but not in most cancers of other organs, may be a significant, underappreciated contributor to the aggressiveness of this disease.